Theme and Thematic Progression in a Recount Text by an Advanced Student - Muhammad Ibnu Mustofa; Eri Kurniawan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Recount text is included within the curriculum of English subjects in the Indonesian context, where students are expected to be well-informed and be able to compose a good recount text to express themselves. The current study aimed at analyzing the recount text written by an advanced (C1 level of English) student based on the concept of Systemic Functional Linguistics. Through a qualitative case study, the data on the text organization, language features, Theme system, and Theme progression of the text were obtained through systematic identification, calculation, and analysis. The findings show that the text fulfilled the text organization and language features of a recount text. Moreover, the types of Themes with the most occurrence were unmarked topical Themes (51,2%), followed by topical textual Themes (40%), marked topical Themes (8%), and interpersonal Themes (0,8%). Based on the Theme system, Theme reiteration occurred most frequently (88.20%), while the Zigzag Themes only represented 11,80% of the total. The dominant use of unmarked Themes demonstrates the writer’s skill in keeping the focus of the readers on the central topic of the text, while the huge number of textual Themes is the implication of the student to maintain the text’s cohesion and coherence.